Auditoría de gestión a los procesos de control de activos fijos y su relación con el patrimonio de la empresa Reybanpac C.A. división lácteos año 2012 - Jácome López, Elvis Omar (2013)
The current project called " Auditing the control processes of fixed assets and its relation to the assets of the company Reybanpac CA Dairy Division , 2012, " it was made in order to provide guidance that , in addition to attest to past operations intended to improve the future operations of the Company Reybanpac CA Dairy Division , because previously there has been no investigation into the audit process to control asset , which allows to know the effective development. Through the project was known that the techniques and procedures used in accordance with COSO standards in the process control of fixed assets are not adequate enough since often only partial tests are performed. The staff involved in assessment processes control in a limited way , by demands of internal rules . It is evident that the application of IAS 1 in the company is being applied correctly, however it is noted that no correlation with IAS 16, which allows a better comparison of the interpretative changes in equity of the company that may lead to d making excellent decisions. For the detection of strengths, weaknesses, opportunities and threats are meetings with the heads of the different areas, which must report on the applications of the procedures and their implementation. However there are difficulties because many times despite identifying conflicts , do not have much time for improvement which staff feel very pressured to try to resolve as quickly as possible and avoid future problems when developing activities .